Scientific Culture Organisational and Professional Identity: A Systemic Game of Contexts and Subjects - Aparicio, Miriam (MASI Mandiri Edukasi, 2024)
In theory, a scientific stratification (branches and disciplines) is frequently associated with the effectiveness of research groups but not professional mobility and other psychosocial factors. The study analyses the relationship among the organisational cultures specific to each field of speciality (human-social sciences versus exact-natural sciences), the satisfaction of researchers and the homogenisation of psychosocial behaviours with the mediation of the professional mobility variable; that is to say, the construction of organisational/disciplinary identities within the scientific system. Quantitative and qualitative techniques were used. Among the first, two questionnaires were used; among the latter, we used non-obstructive observation and interviews. This research concluded that Scientists' psychosocial responses and achievement levels vary according to their speciality areas, highlighting distinct disciplinary and organisational cultures within the scientific community. Dissatisfaction with team leadership is widespread across scientific disciplines, driven by factors such as effort, expectations, and societal influences, necessitating the development of transformative competencies, particularly leadership skills, to address these issues and promote well-being among scientists.